The Structure of Scientific Revolutions: Fifty Years Layer (Richards & Daston, 2016) [In Bulgarian] - B.V. Toshev (University of Sofia, 2016)
Richards, R.I. & Daston, L. (2016). Kuhn's Structure of scientific revolutions at fifty: reflections on a science classic. Chicago: University of Chicago Press, 202 pp. ISBN 978-0-226-31720-5